2001
DOI: 10.1128/jvi.75.24.12288-12297.2001
|View full text |Cite
|
Sign up to set email alerts
|

Double-Stranded RNA-Mediated Interference with Plant Virus Infection

Abstract: Double-stranded RNA (dsRNA) has been shown to play a key role as an inducer of different interference phenomena occurring in both the plant and animal kingdoms. Here, we show that dsRNA derived from viral sequences can interfere with virus infection in a sequence-specific manner by directly delivering dsRNA to leaf cells either by mechanical inoculation or via an Agrobacterium-mediated transient-expression assay. We have successfully interfered with the infection of plants by three viruses belonging to the tob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
159
0
6

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(170 citation statements)
references
References 48 publications
5
159
0
6
Order By: Relevance
“…Recently it was shown that siRNAs of 21 nt in size, an intermediate of the RNA-interference pathway, are effective in suppression of gene expression in animal systems including mammals. Gene silencing induced by long dsRNA constructs has been demonstrated in transgenic plants showing resistance to virus infection (9): transient interference with endogenous gene expression (28), with virus infection in plants (29), and with reporter gene expression in plant cells (30,31). The siRNA technology offers animal virologists a new way to control viruses because the use of long dsRNA triggers the IFN response, which leads to apoptosis in most mammalian cells (32).…”
mentioning
confidence: 99%
“…Recently it was shown that siRNAs of 21 nt in size, an intermediate of the RNA-interference pathway, are effective in suppression of gene expression in animal systems including mammals. Gene silencing induced by long dsRNA constructs has been demonstrated in transgenic plants showing resistance to virus infection (9): transient interference with endogenous gene expression (28), with virus infection in plants (29), and with reporter gene expression in plant cells (30,31). The siRNA technology offers animal virologists a new way to control viruses because the use of long dsRNA triggers the IFN response, which leads to apoptosis in most mammalian cells (32).…”
mentioning
confidence: 99%
“…Previous studies indicate that dsRNA molecules are highly stable in vitro and can persist on the leaves for several days (Tenllado & Diaz-Ruiz, 2001). Thus RNAi technology could be deployed in the field.…”
Section: Resultsmentioning
confidence: 99%
“…RNAi has become a potent tool in many biological research fields ranging from identifying gene function to inhibiting viral infection (Tenllado & Diaz-Ruiz, 2001;Tenllado et al, 2003a). Insect genes can be downregulated by microinjection of dsRNA (Bettencourt et al, 2002;Tomoyasu & Denell, 2004;Ghanima et al, 2007) or uptake of exogenous dsRNA from an artificial diet (Turner et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In productive viral infections, most viruses can counteract the RNA silencing defense, in part by expressing proteins that interfere with the RNA-silencing machinery [43,44]. Silencing of the transgene would target viral RNAs containing enough sequence similarity to the transgene for degradation, therefore inhibiting virus infection [45,46]. The expressed VP2 protein was further analyzed by Western blot analyses for the confirmation of protein expression.…”
Section: Discussionmentioning
confidence: 99%